Logic, language, information, and computation : 22nd International Workshop, WoLLIC 2015, Bloomington, IN, USA, July 20-23, 2015, Proceedings /: 22nd International Workshop, WoLLIC 2015, Bloomington, IN, USA, July 20-23, 2015, Proceedings. (2015) - Unknown
No abstract available